2009
DOI: 10.1002/ppap.200930103
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Investigations of Silicon Carbon Nitride Thin Films Deposited by Magnetron Sputtering

Abstract: Silicon carbon nitride thin films are deposited by sputtering a silicon carbide target under mixed Ar–N2 atmosphere. The flow ratio (RF = [N2]/[N2] + [Ar]) of these two gazes is set between 0 and 1. The deposits were analyzed by Rutherford backscattering (RBS), infrared, Raman, and electron spin resonance (ESR) spectroscopies. Nitrogen content in thin film was found to be sensitive to the sputtering atmosphere until RF = 0.3 and reached a plateau between 0.3 and 1. From a structural point of view, the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…According to Refs. , this C–C band could be described as a random covalent network of tetrahedral–trigonal bonded carbons (mixed sp 2 and sp 3 hybridization) with distorted bond angles and lengths. The broad band at about 2890 cm −1 was attributed to the second‐order phonon of carbon .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Refs. , this C–C band could be described as a random covalent network of tetrahedral–trigonal bonded carbons (mixed sp 2 and sp 3 hybridization) with distorted bond angles and lengths. The broad band at about 2890 cm −1 was attributed to the second‐order phonon of carbon .…”
Section: Resultsmentioning
confidence: 98%
“…It was found that the increase of N concentration leads to the increase of DB densities in a‐SiC x N y films. However, the parameters of the DBs like g ‐value, linewidth and lineshape was not available in the literature . The parameters of the DBs were reported for a‐SiC and hydrogenated C‐rich (a‐Si 1− x C x :H) films.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the molar composition they can exhibit extremely high hardness [1], elevated-temperature creep resistance [2], oxidation resistance at temperatures up to 1600°C [3], low friction coefficient [4], attractive tribological properties [5], tunable optical properties [6,7], and multitude of other desirable properties. Therefore, a-SiC x N y coatings are considered for high temperature wear protective applications due to their excellent thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbonitride films have attracted attention in recent years due to their outstanding physical, chemical, and mechanical properties that stem from the formation of strongly bonded three‐dimensional structural network. In dependence on actual composition, SiCN films can possess high hardness and strength, attractive tribological properties, tunable optical properties, tunable electrical resistivity, excellent abrasive wear, corrosion as well as oxidation resistance characteristics . Recently, the relatively stable hardness of the SiCN coatings with limited N content was proved with in situ high‐temperature nanoindentation measurements up to 650°C .…”
Section: Introductionmentioning
confidence: 99%